Synthesis, Characterization, and Preliminary Antimicrobial Evaluation of New Schiff Bases and Mannich Bases of Isatin - Mustafa Mahmood Mukhlif; May Mohammed Jawad Al-Mudhafar (Iraqi Journal of Pharmaceutical Sciences, 2023)
Till now, isatin derivatives have received a lot of interest in organic and medicinal chemistry due to their significant biological and pharmacological activities. Schiff’s and Mannich bases of isatins are an effective group of heterocyclic derivatives that play a significant role in medicinal chemistry as antimicrobial agents. In light of these facts, new Schiff bases and Mannich bases of isatin were synthesized. The monomer Mannich bases; 3(a-e) have been synthesized by reacting isatin with different secondary amines, piperidine, morpholine, and pyrrolidine, dimethylamine, diphenylamine, separately, and formaldehyde, while the dimer (5) formed by using piperazine and formaldehyde which then react separately with Phenylhydrazine to form new Schiff bases 4(a-e), and dimer Schiff base (6) as final products. The structures of the newly synthesized compounds were identified using two spectroscopic methods; (Fourier- transform infrared) FTIR and proton nuclear magnetic resonance spectroscopy (¹H-NMR) analysis. The preliminary in vitro antibacterial and antifungal screening results of new isatin derivatives [4(a-e) and 6] reported moderate to potent antimicrobial activity, the compound 4c exhibited moderate broad-spectrum antibacterial and antifungal activities compared to other derivatives. Moreover, compounds 4c and 6 have a good inhibitory effect against B. subtilis while amoxicillin (standard drug) shows no activity. For antifungal activity compounds (4a-c and 4e) have considerable activity towards C. albicans, whereas compound 4d exhibits slight activity and 6 of no activity.